Impact of Combined Exercise and High-Intensity Interval Training on 6-Minute Walk Test Dynamics in Heart Failure Patients with Preserved Ejection Fraction: Results from the ExIC-FEp Trial - Iván Cavero-Redondo; Arturo Martínez-Rodrigo; Iris Otero-Luis; Nerea Moreno-Herraiz; Marta Fenoll-Morante; Irene Martínez-García; María José Guzmán-Pavón; Alicia Saz-Lara (Applied Sciences)
(1) Background: Heart failure with preserved ejection fraction (HFpEF) is a clinical challenge, with limited success from current therapeutic strategies. This study aimed to assess the impact of combined exercise (CE) and high-intensity interval training (HIIT) on key biomechanical parameters during the 6-minute walk test (6MWT) in HFpEF patients. (2) Methods: A randomized controlled trial was conducted in 76 sedentary HFpEF patients, divided into three groups as follows: the CE, HIIT, and control groups. CE involves aerobic and strength training, whereas HIIT includes high-intensity intervals. Cadence (steps per minute), distance, maximum heart rate (HRmax), and exercise intensity were measured pre- and postintervention. (3) Results: The results revealed significant improvements in cadence in the CE group compared with the control group (p = 0.009) for intention-to-treat analysis, and in the control and HIIT groups (p = 0.002) for per-protocol analysis. CE also significantly improved HRmax and exercise intensity, suggesting an enhanced cardiovascular response. In contrast, HIIT did not significantly affect these parameters. The correlation between cadence and distance covered during the 6MWT was strong in the overall group (r = 0.762, p < 0.001). (4) Conclusions: These findings suggest that CE is an effective intervention to improve gait efficiency, cardiovascular response, and functional capacity in HFpEF patients, whereas HIIT may require further investigation in this population.